Herbicidas pré-emergentes no controle de plantas daninhas na cultura da soja - Engel, Guilherme Eduardo (2023)
The weeds constitute an obstacle to obtaining high productivity, causing losses of up to 80% in productivity. Weeds compete for nutrients, water, light and space, in addition to serving as a shelter for insects and diseases that can directly affect soybean development. The use of pre-emergence herbicides helps in the management of weeds, especially those that are resistant to herbicides, as they act directly on their seeds, preventing the weed plant from reaching the adult stage, reducing the number of post-emergence applications. The objective of this work was to evaluate the control efficiency of pre-emergent herbicides on weeds in soybean crops, in the sow and apply system. The experiment was carried out in randomized blocks, with four replications, consisting of nine treatments applied one day after soybean sowing, in the sow and apply system, as follows: T1: Flumioxazine, T2: Pyroxasulfone, T3: Flumioxazine + Imazetapyr, T4: Pyroxasulfone + Flumioxazine, T5: S-metolachlor, T6: S-metolachlor + Fomesafen, T7: Sulfentrazone + Imazetapyr, T8: Sulfentrazone + Diuron and T9: Control. The evaluation of the control efficiency of the herbicides was carried out at 7, 14, 21, 28 and 35 days after the application of the herbicides. The assessment of phytotoxicity on soybeans was carried out 7 days after the application of the herbicides. The soybean height and verification of weed species present in the experiment were carried out 35 days after the application of the herbicide and the soybean productivity assessment was carried out at the end of the crop's production cycle, 133 days after sowing. The most efficient treatment in controlling weeds present in the area was the pyroxasulfone + flumioxazine (Kyojin) treatment in all evaluations carried out. There was no significant phytotoxic effect of herbicides on soybeans, only reaching level 4 of having no influence on the crop. The use of some of the pre-emergent herbicides, mainly pyroxasulfone + flumioxazine (Kyojin), resulted in greater weed control and greater productivity, helping in the crop management process